Cooperative activation of O–H and S–H bonds across the Co–P bond of an N-heterocyclic phosphido complex. Issue 9 (13th February 2019) - Poitras, Andrew M.; Bezpalko, Mark W.; Foxman, Bruce M.; Thomas, Christine M.
Abstract : A cobalt N-heterocyclic phosphido complex is shown to cleave element–hydrogen bonds via a metal–phosphorus ligand cooperative pathway. Abstract : Metal–ligand cooperation has proven to be a viable concept for σ bond activation and catalysis, however there are few examples involving phosphorus as an active participant in bond cleavage. The reactivity of E–H bonds (E = S, O) across a metal–phosphorus bond of a cobalt(i ) center ligated by a tridenate N-heterocyclic phosphido (NHP − ) ligand with diphosphine sidearms, (PPP) −, has been explored. Addition of PhOH to (PPP)CoPMe3 (1 ) cleanly affords (PP OPh P)Co(H)PMe3 (2 ), in which the O–H bond was heterolytically cleaved across the M–P NHP bond. Addition of PhSH to1 first generates (PP H P)Co(SPh)PMe3 (3 ), which undergoes an intermolecular rearrangement to generate (PP SPh P)Co(H)PMe3 (4 ) as the thermodynamic product. A comparison with a related platinum(ii ) system reveals the subtle effects that variations in metal intrinsic properties can have on metal–ligand bifunctional σ bond activation processes.